Biomedical and psychosocial aspects of shift work. A review - Rutenfranz, Joseph; Colquhoun, W. Peter; Knauth, Peter; Ghata, J. N. (Scandinavian Journal of Work, Environment & Health, 1977)
A survey of the different types of shift-work systems in use, and the incidence of shift work in different industries and countries, is followed by a discussion of (a) the effects of shift work on health and (b) the physiological problems raised by the phase-shifting of the circadian cycle in night workers. Summaries of the existing knowledge of the effects of shift work on performance efficiency, accidents, and family and social life are then given, and a set of criteria for designing optimal shift systems is proposed. Next, the questions of selection for shift work and the provision of health services for shiftworkers are discussed. Finally, the need for further research on the problems of shift work is explained, and suggestions are offered on the lines such research should follow.
Keywords: accident; attitude; biomedical aspect; biomedicine; circadian rhythm; gastrointestinal disease; interpersonal relationship; performance efficiency; personnel selection; psychosocial aspect; psychosocial factor; review; shift work; sleep